Enlarged perivascular spaces and cognition: A meta-analysis of 5 population-based studies. (28th August 2018) - Hilal, Saima; Tan, Chuen Seng; Adams, Hieab H.H.; Habes, Mohamad; Mok, Vincent; Venketasubramanian, Narayanaswamy; Hofer, Edith; Ikram, M. Kamran; Abrigo, Jill; Vernooij, Meike W.; Chen, Christopher; Hosten, Norbert; et al.
Abstract : Objective: To investigate the association of enlarged perivascular spaces (ePVS) with cognition in elderly without dementia. Methods: We included 5 studies from the Uniform Neuro-Imaging of Virchow-Robin Space Enlargement (UNIVRSE) consortium, namely the Austrian Stroke Prevention Family Study, Study of Health in Pomerania, Rotterdam Study, Epidemiology of Dementia in Singapore study, and Risk Index for Subclinical Brain Lesions in Hong Kong study. ePVS were counted in 4 regions (mesencephalon, hippocampus, basal ganglia, and centrum semiovale) with harmonized rating across studies. Mini-Mental State Examination (MMSE) and general fluid cognitive ability factor (G-factor) were used to assess cognitive function. For each study, a linear regression model was performed to estimate the effect of ePVS on MMSE and G-factor. Estimates were pooled across studies with the use of inverse variance meta-analysis with fixed- or random-effect models when appropriate. Results: The final sample size consisted of 3, 575 persons (age range 63.4–73.2 years, 50.6% women). Total ePVS counts were not significantly associated with MMSE score (mean difference per ePVS score increase 0.001, 95% confidence interval [CI] −0.007 to 0.008, p = 0.885) or G-factor (mean difference per ePVS score increase 0.002, 95% CI −0.001 to 0.006, p = 0.148) in age-, sex-, and education-adjusted models. Adjustments for cardiovascular risk factors and MRI markers did not change the results. Repeating the analyses with region-specific ePVS rendered similar results. Conclusions: In this study, we found that ePVS counts were not associated with cognitive dysfunction in the general population. Future studies with longitudinal designs are warranted to examine whether ePVS contribute to cognitive decline.